José Revueltas y la filosofía latinoamericana: imágenes cinematográficas del mundo (2016)
In this article I argue that the work of Mexican writer José Revueltas Sánchez (1914-1976) moves away from the conventions of Latin American philosophy as it leaves behind the experience of regret and nostalgia for the lost unity as well as the loss of being that was buried under colonialism. I also point out that, in order to achieve this, Revueltas opposes a thought without purpose and a non-moralist analysis of truth. To achieve this, I postulate that Revueltas uses a method based on the construction of a filmic image of thought. This allows him to build a different image of Latin America and its philosophy far from the ethos of suffering and victimization created by Europe. This image is one of Latin America as an island not as a continent.